Economic Education for Muslim Women from the Perspective of the Prophet - Muhammad Zainuddin Nawi; Duski Ibrahim; Mukmin Mukmin (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to identify aspects of economic education for Muslim women based on the orders of the Prophet Muhammad. The research method used is a literature review of the 20 wills of the Prophet Muhammad. The study results indicate that Economic education is crucial for women, especially wives, as societal expectations place them at the forefront of family financial management. Mothers, as primary educators, must master skills for effective economic management, empowering them with financial independence. This education enables informed investment decisions and active contributions to economic development, challenging traditional gender roles. For Muslim women, economic education grounded in Prophet Muhammad's teachings is vital for well-managed lives aligned with Islamic principles. It encompasses ethical wealth management and business ethics, cautioning against extravagant behavior and excessive borrowing. While schools play a pivotal role, oversight may be challenging, but they contribute significantly to preventing behaviors inconsistent with economic prudence.